The Relationships Between Environmental Factors and Phytoplankton Diversity Indices in some Estuarine Ecosystems of Vietnam - Ha, Le Thu; Lien, Nguyen Thuy; Hoa, Bui Thi (VNU Journal of Science: Natural Sciences and Technology, 2016)
Abstract: This study was carried out from 2011, 2012 and 2015 with 4 times at 10 stations of each estuary from 7 estuarine ecosystems. They are Van Uc (Thai Binh river), Ba Lat (Red river), Thuan An (Huong river), Cua Dai (Thu Bon - Vu Gia river), Soai Rap (Dong Nai river), Co Chien (Tien river) and Dinh An (Hau river). The results showed that the physico-chemical parameters are mostly met the standard limit for aquatic lives, except for COD. The salinity level of the estuaries in Center and South are higher than the estuaries in North. Five algal divisions have been found in these estuaries are Bacillariophyta, Chlorophyta, Cyanobacteriophyta, Pyrrophyta and Dinophyta. Among of them, Diatom (Bacillariophyta) was the dominant division at all seven estuaries. The Diatom was the dominant group in density at all surveyed estuaries. The highest H index was recorded at Ba Lat (3.42) and the lowest registered at Soai Rap (2.85). The D index varied from 1.92 (Soai Rap) to 3.17 (Ba Lat). The single environmental variables that best correlated with H index was total N (R 2 = 0.805, p<0.01) and the best correlation was between NO 3 and D index (R 2 = 0.778, p<0.05). Keywords: Environmental factors, phytoplankton diversity, estuaries ecosystems.